CXCR4high megakaryocytes regulate host-defense immunity against bacterial pathogens - Jin Wang; Jiayi Xie; Daosong Wang; Xue Han; Minqi Chen; Guojun Shi; Linjia Jiang; Meng Zhao (eLife, 2022)
Megakaryocytes (MKs) continuously produce platelets to support hemostasis and form a niche for hematopoietic stem cell maintenance in the bone marrow. MKs are also involved in inflammatory responses; however, the mechanism remains poorly understood. Using single-cell sequencing, we identified a CXCR4 highly expressed MK subpopulation, which exhibited both MK-specific and immune characteristics. CXCR4high MKs interacted with myeloid cells to promote their migration and stimulate the bacterial phagocytosis of macrophages and neutrophils by producing TNFα and IL-6. CXCR4high MKs were also capable of phagocytosis, processing, and presenting antigens to activate T cells. Furthermore, CXCR4high MKs also egressed circulation and infiltrated into the spleen, liver, and lung upon bacterial infection. Ablation of MKs suppressed the innate immune response and T cell activation to impair the anti-bacterial effects in mice under the Listeria monocytogenes challenge. Using hematopoietic stem/progenitor cell lineage-tracing mouse lines, we show that CXCR4high MKs were generated from infection-induced emergency megakaryopoiesis in response to bacterial infection. Overall, we identify the CXCR4high MKs, which regulate host-defense immune response against bacterial infection.